AIR MONITORING SYSTEM USING WIRELESS SENSOR NETWORK - Mohd Basha, Muhamad Amir Zahiruddin (Universiti Teknologi PETRONAS, 2021)
Air pollution is a major environmental issue that can risk human health such as high mortality rates, cancer, and cardiovascular disease. That is why air pollution is one of the hot topics for researcher to work on in a project. One of the topics would be an Air Quality Monitoring. In Malaysia, the existing air quality monitoring station requires a lot of money and effort to operate due to its immobility. Moreover, these stations consume a lot of money to install and only the trained staff can operate and do a maintenance for the system. This project will introduce a popular technology for monitoring the air quality especially in Malaysia which is Air Quality Monitoring system using Wireless Sensor Network (WSN). WSN is a technology that allows multiple station nodes communicate with each other by having the same frequency band and the collected data can be stored directly in cloud. The sensors that are being used in this project are MQ-7 to detect carbon monoxide (CO), SEN 0219 to detect carbon dioxide (CO2), Sharp GP2Y1010AUF to detect particulate matter that are smaller than 2.5 microns (PM2.5) and DHT 22 to detect the surrounding temperature and humidity. Communication modules also is needed for implemented WSN such as Lora module and ESP8266 Wi-Fi module.